DEVELOPMENT AND VALIDATION STABILITY INDICATING HPTLC METHOD FOR DETERMINATION OF VILDAGLIPTIN AND METFORMIN HYDROCHLORIDE IN THE PHARMACEUTICAL DOSAGE FORMS - Bendale, Atul R.; Singh, R. P.; Vidyasagar, G. (International Journal of Applied Pharmaceutics, 2018)
Objective: A simple, precise, and accurate stability indicating high-performance thin layer chromatography method was developed and validated of vildagliptin (VIL) and metformin (MET) in pharmaceutical dosage forms. Methods: In the present study, system suitability test, stress study, alkali hydrolysis, acid hydrolysis, neutral hydrolysis, oxidative stress degradation, dry heat degradation, wet heat degradation, photodegradation study has been used. In this method, optimization by changing various parameters, such as organic solvent and the composition of the mobile phase, acid or base modifier used in the mobile phase; by varying one parameter and keeping all other conditions constant. 10 µl of the stock solution for MET (500 ng/band) and 2 µl of the stock solution for VIL (100 ng/band) were applied to TLC plates. The final solutions were applied on the HPTLC plates and these were developed as per the optimized densitometry conditions. Results: From the spectra, it was observed that MET and VIL exhibited good absorbance at about 217 nm. Both the drugs showed degradation with additional peaks at Rfvalues of 0.16 for MET and with Rfvalues 0.81 for VIL respectively. The method was validated for linearity, precision, accuracy, limit of detection, limit of quantification, ruggedness, specificity, and robustness. Good separation was achieved by using the mobile phase Hexane: Methanol: Acetonitrile: Glacial Acetic Acid (2:3.5:2.5:0.2 v/v/v/v) with retardation factor (Rf) values of 0.22±0.01 for MET and 0.73±0.02 for VIL. Conclusion: A validated HPTLC method was developed for the determination of metformin hydrochloride and vildagliptin. The method is simple, quick, and can be applied routinely for the analysis of these drugs from marketed dosage forms.